2011
DOI: 10.1103/physrevb.83.165206
|View full text |Cite
|
Sign up to set email alerts
|

Properties of metal-insulator transition and electron spin relaxation in GaN:Si

Abstract: We investigate the properties of doping-induced metal-insulator transition in GaN:Si by means of electron spin resonance and the Hall effect. While increasing the doping concentration, Si-related bands are formed below the bottom of the GaN conduction band. The D 0 band of single-occupied Si donor sites is centered 27 meV below the bottom of the GaN conduction band, and the D − band of double-occupied Si states is centered at 2.7 meV below the bottom of the GaN conduction band. Strong damping of the magnetic m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 26 publications
5
36
0
Order By: Relevance
“…These estimated values are well above the MIT for n-type GaN:Si of 1.6 × 10 18 cm −3 [31] and theoretical predictions for h-GaN of 1 × 10 18 cm −3 [32]. The 14 N spectrum of GaN:Ge in Figure 1(b) corroborates and extends these conclusions.…”
Section: Fig 2 (Color Online) (A)supporting
confidence: 81%
“…These estimated values are well above the MIT for n-type GaN:Si of 1.6 × 10 18 cm −3 [31] and theoretical predictions for h-GaN of 1 × 10 18 cm −3 [32]. The 14 N spectrum of GaN:Ge in Figure 1(b) corroborates and extends these conclusions.…”
Section: Fig 2 (Color Online) (A)supporting
confidence: 81%
“…34 In a previous study 18 , the g-values were found to be unchanged (within the experimental errors of ∆g=0.0007) in the temperature range of 5-300 K. Our observed increase of the g-value with increasing temperature is similar to the observation in Ref. 17.…”
Section: B Delocalized Donor Electrons and Formation Of Impurity Bandssupporting
confidence: 78%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 correspond to NW length and radius of NID GaN NWs; (g) NW radius variation with the height of the NW, measured along the dashed line in (e). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 determined by Hall measurements for GaN epilayers with different Si doping levels (carrier concentration is designated close to the corresponding line, with a unit of 10 18 cm -3 ) 39 , and the gray dashed line stands for high conducting Si-doped GaN microwire previously reported …”
Section: Notesmentioning
confidence: 99%